2003
DOI: 10.2460/ajvr.2003.64.51
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and systemic effects of ketamine, xylazine, and lidocaine after subarachnoid administration in goats

Abstract: Subarachnoid administration of xylazine in goats resulted in longer duration of analgesia of the tail, perineum, hind limbs, flanks, and caudodorsal rib areas than administration of ketamine or lidocaine. However, xylazine caused bradycardia and respiratory depression. Additional studies are needed to determine whether the analgesia would be sufficient to allow clinicians to perform surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 33 publications
2
44
0
Order By: Relevance
“…Epidural or subarachnoid injection of KE for perineal or flank analgesia in horses 4 , cattle 5,6 and goats 7,27 has been reported previously. Systemically, KE increases arterial blood pressure and stimulates sympathetic activity.…”
Section: Discussionmentioning
confidence: 83%
“…Epidural or subarachnoid injection of KE for perineal or flank analgesia in horses 4 , cattle 5,6 and goats 7,27 has been reported previously. Systemically, KE increases arterial blood pressure and stimulates sympathetic activity.…”
Section: Discussionmentioning
confidence: 83%
“…It has been reported that ketamine administered spinally produced a significant increase in HR, 7 while others did not find any significant changes. 5,6,10 It is known, however, that ketamine is a cardiovascular stimulant, so intramuscular or intravenous administration of ketamine causes an increase in HR and blood pressure. 16,17 In this study, intrathecal injection of ketamine-lidocaine did not induce significant changes in RR and RT.…”
Section: Discussionmentioning
confidence: 99%
“…4 Local anesthetics such as lidocaine hydrochloride, sedatives such as xylazine, and opioids such as butorphanol or their combinations have been used for epidural analgesia in ruminants. 2,3,[5][6][7] In addition, subarachnoid ketamine injection has been advocated for surgeries involving the hind legs, perineum, vulva, and rectum in small ruminants. 7,8 A combination of drugs for the induction of analgesia is usually advantageous over the administration of a single drug.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xylazine is an α 2 -adrenergic receptor agonist sedative with analgesic properties that has a significant effect on depression of the heart rate and the respiratory system (Derossi et al 2003). Tramadol is an effective centrally acting analgesic (Lee et al 1993) that additionally acts as a monoamine reuptake inhibitor (Desmeules et al 1996).…”
mentioning
confidence: 99%